2019
DOI: 10.1186/s12879-019-4433-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sequence types responsible for healthcare-associated Acinetobacter baumannii dissemination in a single centre in Egypt

Abstract: Background Acinetobacter baumannii is an increasingly worrying organism in the healthcare setting, due to its multidrug resistance and persistence. Prolonged hospitalisation, immunocompromised patients and excessive antibiotic exposure all contribute to increasing the risk of A. baumannii infections, which makes cancer patients a significant risk group. This study aims to investigate the dissemination of A. baumannii at the National Cancer Institute (NCI) in Cairo – Egypt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
26
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 22 publications
11
26
2
1
Order By: Relevance
“…In our study, 70% of the isolates were resistant to imipenem, similar to what reported in a study conducted in 2014 [26]. Unfortunately, imipenem resistance in Egypt has recently increased to around 92% of the studied cases [27,28], indicating the decrease of carbepenem effectiveness against A. baumannii infections.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, 70% of the isolates were resistant to imipenem, similar to what reported in a study conducted in 2014 [26]. Unfortunately, imipenem resistance in Egypt has recently increased to around 92% of the studied cases [27,28], indicating the decrease of carbepenem effectiveness against A. baumannii infections.…”
Section: Discussionsupporting
confidence: 89%
“…This was reflected in our study, where oxa23 was carried by 100% of carbapenem-resistant isolates. Reports of the metallo-β-lactamases NDM-1 and NDM-2 being encoded by isolates from Egypt indicate frequencies of blaNDM-1 can typically reach up to 30% (18,71,72), though reports from specific hospitals can occasionally report higher frequencies (16,73). This is in line with our study where 6 isolates (11%) carried a blaNDM-1 gene and only 1 isolate (2%) carried a blaNDM-2 gene.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies of A. baumannii in Egypt have found that rates of carbapenem resistance are high, typically >70% (17,70), and that this is usually associated with isolates carrying the oxa23 gene with carriage frequencies reaching as high as 100% in carbapenem-resistant isolates (16)(17)(18). This was reflected in our study, where oxa23 was carried by 100% of carbapenem-resistant isolates.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations